CpATG8, a Homolog of Yeast Autophagy Protein ATG8, Is Required for Pathogenesis and Hypovirus Accumulation in the Chest Blight Fungus - Shi, Liming; Wang, Jinzi; Quan, Rui; Yang, Feng; Shang, Jinjie; Chen, Baoshan (Frontiers in Cellular and Infection Microbiology, 2019)
Autophagy is a degradation system in the cell, involved in the turnover of cellular components, development, differentiation, immune responses, protection against pathogens, and cell death. Autophagy is induced by nutrient starvation, in which cytoplasmic components and organelles are digested via vacuoles/lysosomes. In this study, by using electron microscopy, we observed that hypovirus CHV1-EP713 infection of Cryphonectria parasitica, the causative agent of chestnut blight disease, caused proliferation of autophagic-like vesicles. This phenomenon could be mimicked by treating the wild-type strain of the fungus EP155 with the autophagy induction drug rapamycin. Some of the hypovirulence-associated traits, including reduced pigmentation and conidiation, were also observed in the rapamycin-treated EP155. Quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) revealed that genes involved in autophagy were up-regulated in expression. Deletion of cpatg8, a gene encoding a homolog of ATG8 in Saccharomyces cerevisiae, resulted in attenuation of virulence and reduction in sporulation, as well as accumulation of the double-stranded viral RNA. Furthermore, virus-encoded p29 protein was found to co-localize with CpATG8, implying that the viral protein may interfere with the function of CpATG8. Taken together, these findings show that cpatg8 can be regulated by the hypovirus and is required for virulence and development of the fungus and accumulation of viral dsRNA in chestnut blight fungus.